2008
DOI: 10.1136/jnnp.2008.152710
|View full text |Cite
|
Sign up to set email alerts
|

Management and clinical outcome of posterior fossa arteriovenous malformations: report on a single-centre 15-year experience

Abstract: The final clinical outcome in PFbAVMs relates directly with the presence of associated aneurysms, number of treatments needed to obliterate the AVM and mRS at presentation. Despite the fact that patients tend to improve after brain AVM haemorrhage, the relationship of MRS at presentation and final outcome suggests that an expedited, more definitive treatment is probably a better choice, especially in patients with good grades after the initial bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 35 publications
0
70
2
Order By: Relevance
“…7 In particular, infratentorial AVMs have been shown to have a higher incidence of associated IAs, hemorrhagic presentation, and unfavorable outcomes. 3,4 In a recent study, AVMs supplied by the posterior circulation, of which 72% were perfusing supratentorial malformations, were found to be more commonly associated with IAs. This finding was suggested to be the result of the interaction between the increased hemodynamic stress due to the presence of the malformation itself and greater peak systolic pressure within the vertebrobasilar system, compared with the anterior circulation.…”
Section: Pathogenesis and Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 In particular, infratentorial AVMs have been shown to have a higher incidence of associated IAs, hemorrhagic presentation, and unfavorable outcomes. 3,4 In a recent study, AVMs supplied by the posterior circulation, of which 72% were perfusing supratentorial malformations, were found to be more commonly associated with IAs. This finding was suggested to be the result of the interaction between the increased hemodynamic stress due to the presence of the malformation itself and greater peak systolic pressure within the vertebrobasilar system, compared with the anterior circulation.…”
Section: Pathogenesis and Demographicsmentioning
confidence: 99%
“…14,20 It is commonly cited that the presence of IAs in patients with AVMs is associated with an increased risk of hemorrhage. 4,6,7,14,[21][22][23] In their meta-analysis, Gross 7,20 while others have found that distal flow-related and intranidal aneurysms that are immediately adjacent to the site of arteriovenous shunting may be more prone to rupture, given the higher flow, pressure, and shear stress on the vessel wall. 8 Finally, the presence of venous ectasia has been found to be inversely related to the risk of hemorrhage, probably reflecting a protective adaptive mechanism that may become more prevalent in older patients.…”
Section: Natural Historymentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Some authors have previously noticed that prenidal aneurysm ruptures were frequent when AVMs were located in the posterior fossa. 2,8,12 We sought to confirm, in a series of cases involving patients with AVMs who were treated at our institution, that patients with posterior fossa AVMs frequently present with hemorrhage associated with prenidal aneurysm ruptures. We also aimed to review the outcome for patients presenting with such ruptures who were treated by endovascular means.…”
mentioning
confidence: 99%
“…Specifically, saccular and fusiform aneurysms arising along the direct course of arterial supply to the AVM are considered “flow-related” [4]. Coexisting aneurysms have been reported in up to 16.7% of cerebral AVMs [5,6,7,8,9,10]. The presence of coexisting unruptured aneurysms is associated with an increased risk of intracranial hemorrhage, with a published risk of 7% per year as compared to patients with AVMs alone with a risk of 3% [5].…”
Section: Introductionmentioning
confidence: 99%